Biosorpsi Logam Cr Dari Limbah Cair Industri Elektroplating Menggunakan Biomassa Alga Biru-Hijau (Anabaena Cycadae) Yang Diimmobilisasi Dengan Silika Gel - Putri, Aulia Dewi; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chromium (Cr) is a heavy metal that has a toxicity and the presence in waters caused by the disposal of wastewater from various industrial activities, one of them is electroplating industry. One of technology that can be applied to reduce the concentration of Cr in the electroplating industry wastewater is biosorption byusing biomass of blue-green algae (Anabaena cycadae) which immobilization with silica gel. This research aims to reducing the concentration of Cr was analyzed using AAS on variation mass of biomass (0.1; 0.2; 0.3; and 0.4 grams), pH of wastewater (3,5, 7, and 9), and the detention time (30, 60, 90, and 120 minutes).The results showed the adsorption capacity of Cr concentration was highest in mass of biomass 0.2 grams, pH 5, and detention time of 30 minutes is 5.79 mg Cr / g biomass.Keywords: Biosorption, Cr, wastewater of electroplating industry, Anabaenacycadae, immobilization, and silica gel